One-Dimensional confined motion of single metal atoms inside Double-Walled carbon nanotubes - Warner, J; Ito, Y; Rümmeli, M; Gemming, T; Büchner, B; Shinohara, H; Briggs, G (2009)
Peapods containing La@C82 metallofullerenes are transformed into double-walled carbon nanotubes (DWNTs) using in situ electron beam irradiation at 80kV. Using this low accelerating voltage we find no damage to the outer single-walled carbon nanotube (SWNT) within this time period and the complete formation of an inner nanotube within 5-7min of irradiation. The La metal atoms are restricted to the interior of the inner SWNT and remain trapped. We demonstrate that energy from electron beam irradiation can drive the lateral confined motion of single La atoms. The interplay between two La atoms confined within the interior of a DWNT is examined and we find large La-La separation unique to this 1D environment. We also demonstrate the formation of TWNTs from DWNT peapods. © 2009 The American Physical Society.